Positive rectal swabs in young patients recovered from coronavirus disease 2019 (COVID-19). Issue 2 (August 2020) - Zhang, Bin; Liu, Shuyi; Dong, Yuhao; Zhang, Lu; Zhong, Qingyang; Zou, Yujian; Zhang, Shuixing
Abstract: Objectives: To investigate the widely concerned issue about positive real-time reverse transcription polymerase chain reaction (RT-PCR) test results after discharge in patients recovered from coronavirus disease 2019 (COVID-19). Methods: We identified seven cases of COVID-19 who was readmitted to hospital because of positive RT-PCR after discharge, including three pediatrics and four young adult patients. Results: Six patients had positive rectal swabs but negative throat swabs, and one patient had positive throat swabs. All the patients continued to be asymptomatic and had unchanged chest computed tomography from previous images. The time from hospital discharge to positive RT-PCR after recovery was 7–11 days. The time from positive to negative rectal swabs was 5-23 days. Conclusion: The study might suggest the positive RT-PCR after recovery did not mean disease relapse or virus reinfection. Adding RT-PCR test of rectal swabs to the criteria for discharge or discontinuation of quarantine might be necessary.